1990
DOI: 10.1002/clc.4960130107
|View full text |Cite
|
Sign up to set email alerts
|

Identification of patients prone to infarct expansion by the degree of regional shape distortion on an early two–dimensional echocardiogram after myocardial infarction

Abstract: Summary:Early detection of potential expanders (patients who develop clinically significant infarct expansion with acute left ventricular (LV) dilatation and failure but no necrosis) after acute myocardial infarction (AMI) is necessary in order to apply preventive therapy. To determine whether the degree of regional shape distortion (RSD), or dilatation, on early two-dimensional echocardiogram (2-D echo) after AM1 can identify potential expanders, serial clinical and echocardiographic data were studied prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…7 Several studies suggested potentially harmful effects with some therapies after MI, 7,13,28,50 -52 supporting caveats against hypotension with vasodilators very early after MI, 50 or impairing healing with powerful anti-inflammatory drugs during early healing. 51 Other post-MI studies demonstrated progressive LV enlargement over 1 year 7,16 or 3 years 52 despite therapy, and morbidity and mortality remain high. 53 In addition, cardiac rupture remains a major cause of death after reperfused MI, 7,39 and the number of post-MI patients needing the LV assist device or awaiting transplantation is increasing, suggesting that protection against LV dilation, adverse ECCM remodeling, decreasing IZ collagen, and impairing healing is needed.…”
Section: Antiremodeling Therapies After Mi: Lessons About Timing Frommentioning
confidence: 99%
See 2 more Smart Citations
“…7 Several studies suggested potentially harmful effects with some therapies after MI, 7,13,28,50 -52 supporting caveats against hypotension with vasodilators very early after MI, 50 or impairing healing with powerful anti-inflammatory drugs during early healing. 51 Other post-MI studies demonstrated progressive LV enlargement over 1 year 7,16 or 3 years 52 despite therapy, and morbidity and mortality remain high. 53 In addition, cardiac rupture remains a major cause of death after reperfused MI, 7,39 and the number of post-MI patients needing the LV assist device or awaiting transplantation is increasing, suggesting that protection against LV dilation, adverse ECCM remodeling, decreasing IZ collagen, and impairing healing is needed.…”
Section: Antiremodeling Therapies After Mi: Lessons About Timing Frommentioning
confidence: 99%
“…First, the LV remodeling process after MI is complex, dynamic, and time dependent, and progresses in parallel with healing over months. 1,2,7,16 Notably, it involves differential changes between the IZ and NIZ with respect to the following: (1) LV structure, shape, and topography 1,2 ( Figure 1); (2) cell type, such as myocytes and nonmyocytes (Table 1) 6,7,[17][18][19][20][21][22][23] ; (3) proteins, cytokines, and growth factors 7,24,25 ; and (4) the ECCM. 5-7,13-17,19 -23 Differential regional remodeling of the ECCM contributes significantly to global LV structural remodeling after MI ( Figure 2) 7,9,26 and plays a pivotal role in paradigm 1.…”
Section: Ventricular Remodeling After MI and The Role Of Eccmmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventy-five healthy mongrel dogs (weight, 16 to 29 kg) of either sex were instrumented through a left lateral thoracotomy under general anesthesia (sodium pentobarbital, 30 mg/kg IV), as described previously. 25 (11 control, 11 nitrate).…”
Section: Experimental Preparationmentioning
confidence: 99%
“…Nevertheless, a variety of potential tar gets for limiting postinfarct remodelling has been identi fied (table 1) [81], It is clear that a successful strategy is likely to involve a combination of interventions that pro vide additive, or even synergistic, benefits by altering one or more factors that influence infarct remodelling (ta ble 2) [81], For the primary prevention of cardiac remod elling, the optimal strategy based on current evidence should involve intervention that is instituted very early after the initial event, spans the entire healing process and continues well beyond [81]. A secondary prevention strat egy is also warranted for the early identification and treat ment of patients who already show evidence of cardiac remodelling after AML 32 Cardiology 1997:88(suppl 1 ):26-35 V isser…”
Section: The Need For Multiple Interventionsmentioning
confidence: 99%